1103 How to Report Noise in The Operating Theatre. (12th October 2021) - Thompson, N; Hampton, T; Everett, S; Krishnan, M
Abstract: Introduction: The reporting of operating theatre noise in the surgical literature dates back almost 50 years. The existing standards for noise and sound reporting in healthcare settings is heterogenous and there is a need for greater uniformity of reporting to support our growing understanding of the significance of communication and human factors on surgical performance. Method: This presentation summarizes the existing Surgical and Acoustic Engineering industrial expertise to provide a narrative review of literature, grey reports and guidelines and then demonstrates appropriate reporting standards during Noise level recording in an operating theatre environment. Results: We describe LAmax, LA90 and LAeq expected levels. We compare our own theatre noise levels against these recommended standards for comparison. This presentation also suggests a suitable "ambient noise" (LAeq 65dB) level over which any communication devices or communication studies should benchmark when developing interventions to overcome noise in the operating theatre. Conclusions: This paper proposes possible unified reporting standards and expected sound pressure levels against which future studies in this field could benchmark.